Evaluation of a laboratory model test using field measurements of frost penetration in railway tunnels - Andrén, Anna; Dahlström, Lars-Olof; Nordlund, Erling (Cold Regions Science and Technology, 2022)
Despite extensive grouting efforts to prevent water from leaking into tunnels, water seepages remain. When exposed to freezing temperatures, ice formations occur. During the winter, the Swedish Transport Administration's railway tunnels are affected by major problems caused by ice, such as icicles from roof and walls, ice loads on installations, ice-covered tracks and roads, etc. To ensure safety and prevent traffic disruptions, many tunnels require extensive maintenance. Improved knowledge about frost penetration in tunnels is required to reduce maintenance of the tunnels. Frost insulated drain mats are often used at leakage spots to prevent ice formation along the tunnels. To find out which parts of a tunnel are exposed to freezing temperatures, the University of Gävle and the Royal Institute of Technology in Stockholm conducted a laboratory model test on behalf of the Swedish National Rail Administration (now the Swedish Transport Administration). The laboratory model test aimed to find a method to determine the expected temperature conditions along a tunnel to decide which parts of the tunnel require frost insulation to protect the drainage system from freezing and prevent ice formation. To evaluate the laboratory model test, the Swedish Transport Administration in collaboration with Luleå University of Technology have performed field surveys in two Swedish railway tunnels. The field measurements involved monitoring temperatures in air, rock surfaces and rock mass, as well as measuring wind direction, wind and air velocity and air pressure. The measurements in the tunnels show that the frost penetrates further into the tunnels than was expected from the laboratory model test, which was based on a completely uninsulated tunnel. Frost insulated drains do not only prevent the cold air from reaching the rock mass, but also prevent the rock from emitting geothermal heat that warms up the cold tunnel air. Consequently, the frost penetrates further into the tunnel than it would do if the heat from the rock mass was ...